Determinants of environmental, social, and governance (ESG) disclosure in Indonesian banking sector - Silvia, Anis; Hadiyati, Siti Nur (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2026)
This study intends to investigate the influence of corporate governance systems on the level of Environmental, Social, and Governance (ESG) Disclosure in the banking industry listed on the Indonesia Stock Exchange. The variables analyzed include Independent Board of Commissioners, Board Size, Audit Committee Expertise, Independent Audit Committee, and Institutional Ownership. This research takes a quantitative method with secondary data acquired from annual reports and sustainability reports over a three-year period. The research sample consists of 39 banks that match the sample selection criteria. Multiple linear regression was used to analyze the data. The research findings indicate that an Independent Board of Commissioners, Board Size, an Independent Audit Committee, and Institutional Ownership exert a positive and significant influence on ESG Disclosure. Meanwhile, Audit Committee Expertise has a positive but insignificant impact on ESG Disclosure. These results suggest that how a company is managed, particularly through careful oversight and pressure from outside sources, is important for improving transparency in ESG Disclosure in the banking industry.